The Rights of the Non-Muslims During the Rule of the Prophet Mohammed and Rashidians Succession Theoretically With Historical Witnesses (Journal of the College of Education for Women, 2019)
(Thimma) in Arabic means compact, and immunity. (People of Thimma) are the free non-Muslim people under Muslim rule. This includes Heavenly Religions people, i. e., Christian and Jews).They have been called (People of Thimma) because they had paid (Jizyah: tribute) so they became safe for their souls, honor, properties at the custody of Muslims.Islamic law had posed (Jizyah: tribute) upon the Jews and Christians who were living under Muslim rule as a reaction of not embracing Islam Faith against securing their rights and freedom.Freedoms secured by Islam for the (People of Thimma) had been many, including the right of faith, not coercing them to be Muslim, the right to live, to possess properties, protect and secure them, their right to make use of the state facilities in addition to their freedom to practice their religious rituals.There are numerous Quranic verses, and Prophetic traditions which clarify the rights enjoyed by Christian and Jew people. There are also a great deal of historic evidence which confirm these people's enjoyment of their rights and their freedom under Muslim rule.